THE PHYTOCHEMICAL TEST AND ANTIOXIDANT ACTIVITY (DPPH METHOD) FROM LEAVES OF BIRIBA (Rollinia mucosa (Jacq.) Baill.) - Sumarni, Feni; Saleh, Chairul; Pratiwi, Djihan Ryn (Jurusan Kimia FMIPA UNMUL, 2019)
Phytochemical test and antioxidant activity test of biriba leaves (Rollinia mucosa (Jacq.) Baill.) has been done. Extraction from biriba leaves was carried out using several solvents, namely ethanol, n-hexane and ethyl acetate. From phytochemical test results from leaves of biriba (R. mucosa) containing secondary metabolites namely alkaloids, phenolics, flavonoids and steroids. Based on the results of the antioxidant test using DPPH (1,1-diphenyl-2-picrylhidrazyl) method showed that the crude extract, n-hexane fraction, ethyl acetate fraction and residual ethanol fraction had IC50 values of 159.72; 119.62; 40.12 and 38.35 ppm, respectively. From the results of the antioxidant test it is known that the ethanol fraction of the remaining biriba leaves has the strongest antioxidant activity with IC50 values of 38.35 ppm.